Growth and scintillation properties of NaLa(WO₄)₂ and NaLa(MoO₄)₂ single crystals - Baumer, V.N.; Gorobets, Yu.N.; Kosmyna, M.B.; Nazarenko, B.P.; Puzikov, V.M.; Shekhovtsov, A.N.; Zelenskaya, O.V. (Functional Materials, 2008)
Pure and doped NaLa(WO₄)₂ and NaLa(MoO₄)₂ single crystals have been grown by the Czhochralski technique. The scintillation characteristics thereof have been determined and considered. Методом Чохральського вирощено чисті та активовані монокристали подвійного вольфрамату NaLa(WO₄)₂ та молібдату NaLa(MoO₄)₂. Визначено та проаналізовано їхні сцинтиляційні характеристики. Методом Чохральского выращены чистые и активированные монокристаллы вольфрамата NaLa(WO₄)₂ и молибдата NaLa(MoO₄)₂. Определены и проанализированы их сцинтилляционные характеристики.